From Tradisional to Certified: Pelatihan Penyusunan Standart PIRT dan Sertifikasi Halal bagi UMKM Kripik Tempe Majenang - Muhammad Ngasifudin; Inngamul Wafi; Tri Almunawaroh; Sinta Dewi Safingah; Cici Widianingsih (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Until now, tempe chips produced in the Majenang area have only been sold to shops and stalls in the surrounding area. Due to simple packaging, a lack of knowledge in the use of promotional media, inadequate facilities and employees, production has been limited. In addition, they do not yet have a distribution permit from the Health Office in the form of a PIRT certificate for home industries, as well as a halal certificate to guarantee the halal status of the product. The purpose of this community service is to provide assistance to help Tempe Chip MSMEs meet the legality requirements for distribution permits with the issuance of SPP-IRT and Halal Certificates. This activity uses a 4-stage assistance method. Namely, the data collection stage, the socialization stage, the document preparation stage, and the registration stage through the system. As a result, business actors are now more aware of the importance of legality as a guarantee of quality and a strategy to increase competitiveness. Some participants have successfully applied for PIRT permits and halal certification, while also improving production management and packaging design in accordance with regulatory standards. With the halal and PIRT labels, it is hoped that consumer confidence will be strengthened, thereby increasing sales and expanding the market.